Early Surgery Prolongs Professional Activity in IDH Mutant Low-Grade Glioma Patients: A Policy Change Analysis - Robe, Pierre A.; Rados, Matea; Spliet, Wim G.; Hoff, Reinier G.; Gosselaar, Peter; Broekman, Marike L. D.; van Zandvoort, Martine J.; Seute, Tatjana; Snijders, Tom J. (Frontiers in Oncology, 2022)
Background Until 2015, Dutch guidelines recommended follow-up and biopsy rather than surgery as initial care for suspected low-grade gliomas (LGG). Given evidence that surgery could extend patient survival, our center stopped following this guideline on January 1st, 2010 and opted for early maximal safe resection of LGG. The effects of early surgery on the ability to work of the patients remains little documented. Methods 104 patients operated at our center between 01/2000 and 04/2013 and diagnosed with WHO 2016 grade 2 astrocytoma, IDH mutant or oligodendroglioma, IDH mutant and 1p19q deleted were included. The clinical characteristics, survival and work history of patients operated before or after January 2010 were obtained from the patients’ records and compared. The minimal follow-up was 8 years. Results As per policy change, the interval between radiological diagnosis and first surgery decreased significantly after 2010. Likewise, before 2010, 25.8% of tumors were initially biopsied, 51.6% were resected under anesthesia and 22.5% under awake conditions, versus 14.3%, 23.8% and 61.9% after this date (P<0.001). The severity of permanent post-operative neurological deficits decreased after 2010. 82.5% of the patients returned to work postoperatively before 2010, versus 100 % after 2010. The postoperative control of epilepsy increased significantly after 2010 (74.4% vs 47.9%). The median time from diagnosis to a definitive incapacity to work increased by more than 2 years after 2010 (88.7 months vs. 62.2 months). Conclusion A policy shift towards early aggressive surgical treatment of IDH mutant LGG is safe and prolongs the patients’ ability to work.